SPECT imaging of cerebral blood flow changes induced by acute trigeminal nerve stimulation in drug-resistant epilepsy. A pilot study. Issue 6 (June 2021) - Mercante, Beniamina; Nuvoli, Susanna; Sotgiu, Maria A.; Manca, Andrea; Todesco, Sara; Melis, Francesco; Spanu, Angela; Deriu, Franca
Highlights: Patients with drug-resistant epilepsy showed global hypoperfusion at brain SPECT. After trigeminal nerve stimulation perfusion increased in the temporal and limbic lobes. TNS effects may reflect activity changes in cortical areas associated to epilepsy. Abstract: Objective: To explore the cortical areas targeted by acute transcutaneous trigeminal nerve stimulation (TNS) in patients with drug-resistant epilepsy (DRE) using single photon emission computed tomography (SPECT). Methods: Ten patients with DRE underwent brain SPECT at baseline and immediately after a 20-minute TNS (0.25 ms; 120 Hz; 30 s ON and 30 s OFF) applied bilaterally to the infraorbital nerve. The French Color Standard International Scale was used for qualitative analyses and z-scores were used to calculate the Odds Ratio (OR). Results: At baseline global hypoperfusion (mainly in temporo-mesial, temporo-parietal and fronto-temporal and temporo-occipital areas) was detected in all patients. Following TNS, a global increase in cortical tracer uptake and a significant decrease in median hypoperfusion score were observed. A significant effect favoring a general TNS-induced increase in cortical perfusion (OR = 4.96; p = 0.0005) was detected in 70% of cases, with significant effects in the limbic (p = 0.003) and temporal (p = 0.003) lobes. Quantitative analyses of z-scores confirmed significant TNS-induced increases in perfusion in the temporal (+0.59 SDs; p = 0.001), and limbic (+0.43 SDs; p = 0.03) lobes. Conclusion: Short-term TNS is followed a global increase in cortical perfusion, namely in the temporal and limbic lobes. Significance: The TNS-induced perfusion increase may reflect neurons' activity changes in cortical areas implicated in the epilepsy network.